Factors influencing effectiveness in second-tier marketing RPOs in Uganda - Ampaire, Edidah; Macheth, Charles (International Food Policy Research Institute, 2012)
This paper investigates the factors influencing the effectiveness of second-tier rural producer organizations (RPO) in linking their members to output markets in Uganda. Effectiveness of an RPO is expressed as the percentage of farmer members who used the RPO for marketing some of their production in 2009. To identify factors that influence RPO effectiveness, a censored least absolute deviations estimator regression was run. The explanatory variables considered as possible factors that influence RPO effectiveness included democratic governance mechanisms, the skills of leaders, RPO size, financial base, gender composition of the membership, and bulking distance. Results show that RPO size, democratic leadership and higher proportions of women membership in RPOs have a significant positive effect on RPO effectiveness. On the other hand, the proportion of RPO leaders trained in leadership and involved in related business activities have a significant negative effect on RPO effectiveness.